2022
DOI: 10.3390/cells11071100
|View full text |Cite
|
Sign up to set email alerts
|

WRKY Gene Family Drives Dormancy Release in Onion Bulbs

Abstract: Onion (Allium cepa L.) is an important bulb crop grown worldwide. Dormancy in bulbous plants is an important physiological state mainly regulated by a complex gene network that determines a stop of vegetative growth during unfavorable seasons. Limited knowledge on the molecular mechanisms that regulate dormancy in onion were available until now. Here, a comparison between uninfected and onion yellow dwarf virus (OYDV)-infected onion bulbs highlighted an altered dormancy in the virus-infected plants, causing se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 86 publications
(135 reference statements)
0
5
0
Order By: Relevance
“…This knowledge is critical to dissecting the regulatory networks of this complex trait. The transcriptomic approach contributed to understanding the changes regulating crop responses to abiotic stress such as low N availability as well as to identifying key genes related to N-stress tolerance comparing NUE-contrasting genotypes (Goel et al, 2018;Sinha et al, 2018;Subudhi et al, 2020;Sultana et al, 2020;Mauceri et al, 2021;Puccio et al, 2022). In tomato, transcriptomic analyses led to the identification of genes differentially regulated by N availability (Wang et al, 2001;Renau-Morata et al, 2021), while no comparative transcriptome profiling between NUE-contrasting genotypes in response to N starvation and resupply has been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge is critical to dissecting the regulatory networks of this complex trait. The transcriptomic approach contributed to understanding the changes regulating crop responses to abiotic stress such as low N availability as well as to identifying key genes related to N-stress tolerance comparing NUE-contrasting genotypes (Goel et al, 2018;Sinha et al, 2018;Subudhi et al, 2020;Sultana et al, 2020;Mauceri et al, 2021;Puccio et al, 2022). In tomato, transcriptomic analyses led to the identification of genes differentially regulated by N availability (Wang et al, 2001;Renau-Morata et al, 2021), while no comparative transcriptome profiling between NUE-contrasting genotypes in response to N starvation and resupply has been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…Each replicate included a pool of healthy fully expanded leaves taken from all the plants in the pots. Sequence libraries were prepared as reported in Puccio et al 101 using a TruSeq RNA Sample Preparation Kit v2 (Illumina, San Diego, CA, USA). Both quality and insert size distribution by using an Agilent Bioanalyzer DNA 1000 chip were assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Reverse transcription was performed on 200 ng of total RNA extracted from AM− and AM + samples, using iScript Reverse Transcription Supermix (Bio-Rad, Berkeley, CA, USA), according to manufacturer’s instructions. qPCR was performed as described in Puccio et al 101 , starting from 20 ng of cDNA 101 . Three biological and three technical replicates were analyzed for each sample (AM + and AM−).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the TdNRT2s upstream region was also highly enriched with MYB binding sites, as shown by both CREs and TF binding site prediction. MYB TFs are often involved in abiotic and biotic stress responses as well as in plant development, root and flower development (Kaur et al, 2017), although their role in NO 3 related regulation has also been reported (Todd et al, 2004;Wang et al, 2018a;Zhang et al, 2021;Puccio et al, 2022). Interestingly, both gene family promoters showed multiple putative MYB binding sites for many genes.…”
Section: Discussionmentioning
confidence: 99%